2008
DOI: 10.1055/s-2008-1027221
|View full text |Cite
|
Sign up to set email alerts
|

Biophysikalische Grundlagen der Kollagenvernetzung

Abstract: The therapy parameters were tested experimentally and have been proven clinically in the corneal collagen cross-linking. These parameters should be respected to reach a safe cross-linking effect without damage of the adjacent tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 51 publications
(49 reference statements)
1
11
0
4
Order By: Relevance
“…Usually, the riboflavin solution is administered for 15 to 30 minutes before the actual UVA irradiation and every 3 minutes during the CXL treatment. 1,2,4,5 The riboflavin within the stroma has the dual role of enhancing UVA absorption as a photosensitizer, leading to collagen crosslinking, and acting as a protective substance by shielding the deeper ocular structures (eg, endothelium, lens, retina) from UVA irradiances that are too high. 5,6 The main role of the preocular riboflavin film has been thought to be to prevent dehydration 1,7,8 and to maintain the riboflavin steady-state equilibrium within the corneal stroma, allowing a continuous riboflavin source.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, the riboflavin solution is administered for 15 to 30 minutes before the actual UVA irradiation and every 3 minutes during the CXL treatment. 1,2,4,5 The riboflavin within the stroma has the dual role of enhancing UVA absorption as a photosensitizer, leading to collagen crosslinking, and acting as a protective substance by shielding the deeper ocular structures (eg, endothelium, lens, retina) from UVA irradiances that are too high. 5,6 The main role of the preocular riboflavin film has been thought to be to prevent dehydration 1,7,8 and to maintain the riboflavin steady-state equilibrium within the corneal stroma, allowing a continuous riboflavin source.…”
mentioning
confidence: 99%
“…1,2,4,5 The riboflavin within the stroma has the dual role of enhancing UVA absorption as a photosensitizer, leading to collagen crosslinking, and acting as a protective substance by shielding the deeper ocular structures (eg, endothelium, lens, retina) from UVA irradiances that are too high. 5,6 The main role of the preocular riboflavin film has been thought to be to prevent dehydration 1,7,8 and to maintain the riboflavin steady-state equilibrium within the corneal stroma, allowing a continuous riboflavin source. 5,6 Using riboflavin solutions of different composition, we recently noted a difference in viscosity, thickness, and stability of various solutions, especially the hypoosmolar riboflavin solution, which was introduced to artificially swell thin corneas to at least 400 mm to reduce the cytotoxic risk to the endothelium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 With advances in photopolymerization made in the 1990s at Dresden University, Germany, 2,3 research was undertaken into the efficacy of methods of polymerization in the treatment of corneas affected by keratoconus. 4,5 Basic studies showed the potential of photopolymerization induced by irradiation with ultraviolet A (UVA) (wavelength 360 nm) after application of riboflavin 0.1% in deepithelialized corneas to induce corneal stiffening while maintaining structural integrity and corneal transparency and preserving corneal and ocular anatomical and histological structures (endothelium, lens, and retina). 6,7 The parameters emerging from the Dresden research, 2,3,4 subsequently confirmed in other studies, 8,9 envisage debridement of corneal epithelium to obtain crosslinking to a depth of at least 250 to 300 mm into the corneal stroma 10,11 using an energy of 3 mW/cm 2 of 360 nm wave light for a total exposure time of 30 minutes.…”
mentioning
confidence: 99%
“…4,5 Basic studies showed the potential of photopolymerization induced by irradiation with ultraviolet A (UVA) (wavelength 360 nm) after application of riboflavin 0.1% in deepithelialized corneas to induce corneal stiffening while maintaining structural integrity and corneal transparency and preserving corneal and ocular anatomical and histological structures (endothelium, lens, and retina). 6,7 The parameters emerging from the Dresden research, 2,3,4 subsequently confirmed in other studies, 8,9 envisage debridement of corneal epithelium to obtain crosslinking to a depth of at least 250 to 300 mm into the corneal stroma 10,11 using an energy of 3 mW/cm 2 of 360 nm wave light for a total exposure time of 30 minutes. Experimental data on the penetration of UVA radiation and its effects ex vivo 12 were confirmed in vivo in humans by confocal microscopy studies 11,13,14 in patients with keratoconus treated by the standardized procedure.…”
mentioning
confidence: 99%